2003
DOI: 10.4049/jimmunol.170.12.6165
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Their Derived Peptides as Carriers in a Conjugate Vaccine forStreptococcus pneumoniae: Self-Heat Shock Protein 60 and Tetanus Toxoid

Abstract: We induced T cell help for vaccination against Streptococcus pneumoniae (Pn) using self and foreign peptides and their source proteins conjugated to the capsular polysaccharide (CPS) of type 4 Pn; the carriers were self-heat shock protein 60 (HSP60) and tetanus toxoid (TT). We measured the production of IgG Abs to the CPS and the carriers, and tested resistance to challenge with highly lethal amounts of Pn injected i.p. (LD50 × 103–106). We now report that vaccination protects old and young mice from bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…9 that some of the mice vaccinated with BMDC produced very little or no detectible IgG or IgM Abs, but were, nevertheless, protected against the challenge. We have previously reported that some mice vaccinated with the PS4-p458 conjugate made very little detectible Ab, yet were still resistant to supralethal S. pneumoniae challenge (14). Similarly, RAW cells pulsed with PS4 induced protection to 100 ϫ LD 50 bacteria for 3 mo, but no IgG or IgM Ab could be detected in the sera of the injected mice by a variety of assay systems (data not shown).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…9 that some of the mice vaccinated with BMDC produced very little or no detectible IgG or IgM Abs, but were, nevertheless, protected against the challenge. We have previously reported that some mice vaccinated with the PS4-p458 conjugate made very little detectible Ab, yet were still resistant to supralethal S. pneumoniae challenge (14). Similarly, RAW cells pulsed with PS4 induced protection to 100 ϫ LD 50 bacteria for 3 mo, but no IgG or IgM Ab could be detected in the sera of the injected mice by a variety of assay systems (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…The conjugates were made as previously described (14). Briefly, PS4 was dissolved in double-distilled water (5 mg/ml) and was activated with 0.1 ml of cyanogen bromide (20 mg/ml in acetone) in the presence of 30 mM triethylamine (Sigma-Aldrich) in acetone (pH 7).…”
Section: Ps4 Conjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…20 For these reasons, I and my colleagues have developed conjugate vaccines based on combining a specific pathogen epitope with a peptide epitope of the mammalian HSP60 molecule. We have used a peptide of self-HSP60, termed p458, to formulate subunit vaccines by conjugating p458 to various pathogen virulence molecules such as the capsular polysaccharides (CPS) of Salmonella, 21 Pneumococcus 22 or Meningococcus types C and B. 23 Some bacterial HSP60 peptides too are agonists for effective innate receptors, and can also serve in effective conjugate vaccines; the phenomenon is not limited to self.…”
Section: Hsp60 Conjugate Vaccinesmentioning
confidence: 99%
“…1). Note that these conjugate vaccines are effective without the need for added adjuvant, [21][22][23] a factor that adds to safety. The detailed results can be seen in the publications.…”
Section: Hsp60 Conjugate Vaccinesmentioning
confidence: 99%